Pengaruh Kepemilikan Institusional, Arus Kas Bebas terhadap Kebijakan Dividen dan Volatilitas Harga Saham (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Prabowo, Satriya Candra Bondan; Salim, Ubud (Jurnal Aplikasi Manajemen, 2013)
The manufacturing company’s ability to face economic fluctuation finally influences the policy making, including dividend policy; also, the ownership composition of manufacturing companies in Indonesia that mostly are dominated by institution attracts a research on investigating the agency relation in the developing countries. It is due to that agency theory initially occurs at developed countries in which the stock ownership is spread , not like in Indonesia. Among the manufacturing companies that are listed at Indonesian Stock Exchange, only a few stockholders that have incentive and ability to control and monitor the management’s decision and activities; thus, the agency problem will emerge so that dividend becomes an important issue which influences the company stock’s price volatility. The research aims to 1) know the influence of institutional ownership to dividend policy 2) know the influence of free cash flow to dividend policy 3) know the influence of institutional ownership to stock price volatility, 4) know the influence of free cash flow to stock price volatility 5) know the influence of dividend policy to stock price volatility, 6) know the influence of institutional ownership to stock price volatility through dividend policy, and 7) know the influence of free cash flow to stock price volatility through dividend policy. This is an explanatory research as it explains the causal relationship among researched variables through hypothesis testing. The research samples are 12 manufacturing companies. Further, the data analysis is conducted by using path analysis. The results of the research are 1) institutional ownership directly influences dividend policy, 2) free cash flow directly influences dividend policy, 3) institutional ownership does not directly influence stock price volatility, 4) free cash flow directly influences stock price volatility, 5) dividend policy directly influences stock price volatility 6) dividend policy is able to mediate institutional ownership’s influence on stock price volatility, and 7) dividend policy is able to mediate the free cash flow’s influence on stock price volatility.